Equivocation in the theatre of the absurd : discourse analysis - Abedi, Haidar K. al- (Logos Verlag Berlin GmbH, 2015)
Long description: This book is the first attempt made to analyse the equivocal language of the Absurd Theatre via pure linguistic models carefully employed and illustrated by a wide range of significant examples, questions, and discussions. It provides the multiple tools necessary for understanding this language from various perspectives. Dr. Haidar K. Al-Abedi was Lecturer in English at University of Baghdad, Al-Muthana University, and Al-Israa University College. ``Haidar has to be complimented at the outset for selecting a very interesting topic . . . It is not surprising that a person from Iraq - and the ravages the country is sadly facing these days - is interested in an area which has its significant socio-cultural origin in the ravages of the World War II. The scope of the research also effectively covers the entire school of the British exponents of the Absurd Theatre. In fact, the first chapter discusses the central keyword - equivocation - in scholarly detail. There is an interesting discussion about the various types of equivocation from chapter two to five quite elaborately conducted by the researcher.'' Dr. Sanjay Mukherjee, Saurashtra University, India ``This book is an elaborate analysis of a number of plays written by different dramatists. By elucidating the equivocal verbal and non-verbal communication used by characters, the book addresses a wide range of social, religious, cultural, and political themes and issues which appeal to its audience/readers and are involved in constructing meaning through its peculiar use of language.'' Dr. Adel Saleh, Wasit University, Iraq.